Correlation of Specific Inflammatory Markers With the Occurrence of Depression in Patients With Psoriasis and Their Use as Biomarkers for the Diagnosis Of Depression - Eleni Mitsiou; Aikaterini Kyriakou; Eleni Parlapani; Anastasia Trigoni; Myrto Trakatelli; Zoe Apalla; Dimitrios Sotiriadis; Elizabeth Lazaridou; Aikaterini Patsatsi (Mattioli1885, 2024)
Introduction: Psoriasis is a systemic disease of the skin and nails associated with a wide range of comorbidities such as depression, psoriatic arthritis  and metabolic syndrome.  Objective: The study aimed to examine a potential association between inflammatory markers (CRP, ESR) and depression in patients with psoriasis. Material and methods: A total of 80 individuals were enrolled in the study. Case participants included 28 patients diagnosed with Psoriasis (Beck Depression Inventory-II: :0-13) and 24 patients diagnosed with Psoriasis and Depression (Beck Depression Inventory-II:14-63). Twenty-eight (28) healthy participants comprised the control group. Psoriasis severity was evaluated by using Psoriasis Area and Severity Index, Physician Global Assessment, Body Surface Area and Dermatology Life Quality Index . Written approval was obtained for its use in this study: Cardiff University (09/2015). Other factors considered in the study were obesity using the Body Mass Index, the levels of stress using the Beck Anxiety Inventory, and the presence of insomnia using the Athens Insomnia Scale . Blood draws and inflammatory markers measurements were performed for all participants. Results: Both CRP and ESR levels were higher in the case group (i.e. Psoriasis and Depression and Psoriasis) compared to healthy controls. Furthermore, psoriatic patients with depression showed increased CRP and ESR levels compared to those of psoriatic patients without depression. Conclusions: The evaluation of both CRP and ESR and their use to detect the presence of depression in patients with psoriasis can be an important tool for their holistic treatment of theirs.